The Influence of Corporate Social Responsibility, Organizational Commitment, Transformational Leadership Style and Internal Control System on Organizational Reputation: Palm Oil Companies - Fitriansyah, Arya Haqi; Hizazi, Achmad; Lady Silvera , Dica (Jurnal Cakrawala Akuntansi, 2025)
The This study aimed to identify the influences corporate social responsibility, organizational commitment, transformational leader-ship style and internal control system on organizational reputation. Data from four companies with 38 respondents were collected using a Google form or direct questionnaire sent to Palm Oil companies and analyzed using the multiple-linear regression analysis with SPSS 30. The study's findings suggest that organizational commitment, transformational leadership style, and corporate social responsibility all have some bearing on an organization's reputation. On the other hand, reputation is not significantly impacted by the internal control system. This finding imply that companies should keep giving the internal control system top priority in order to promote further advancements. This study makes a contribution by providing a thorough examination of organizational commitment, transformational leadership, CSR and the internal control system. The study offers a more comprehensive understanding of how organizational reputation is formed by combining these variables into a single model. This study is an improvement from earlier research that usually investigates at these factors separately in restricted combinations.